Characterization of Flakes Made in Corn Flour (Zea Mays) and Pumpkin (Cucurbita Moshcata) with Addition of Soybean Flour (Glicine Max) - Lucia Saraswati; Fauzan Azima; Daimon Syukri (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2022)
ABSTRACT This study aims to determine the effect of adding soybean flour (Glicine max) to the chemical, physical, and organoleptic characteristics of flakes from a combination of corn (Zea mays) and pumpkin (Cucurbita moshcata) and to determine the best treatment for flakes produced based on chemical, physical characteristics, and it's organoleptic. The research method used is an experimental method with descriptive data analysis. This study used 5 treatments and 3 replications: A = (addition of 0 grams of soybean flour), B = (addition of 15 grams of soybean flour), C = (addition of 30 grams of soybean flour), D = (addition of 45 grams of soybean flour), and E = (addition of 60 grams of soybean flour). Observations made were chemical analysis in the form of water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, and total amino acids in treatment C, as well as physical tests in the form of water absorption tests, color tests, and organoleptic tests in the form of color, aroma, taste, and texture. The results showed that the addition of soybean flour in the study of corn and pumpkin flour flakes affected water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, water absorption, brightness (color), and preference level based on the color, flavor, taste, and texture of the resulting flakes. The best treatment of flakes produced was treatment C (addition of 30 grams of soybean flour) based on the panelists' preference level with quality characteristics, is: water content (6.43% ± 0.41), ash content (1.76% ± 0.19), protein content (9.78% ± 0.29), fat content (11.25% ± 0.69), carbohydrate content (70.89% ± 0.57), crude fiber content (2.81% ± 0.29), water absorption 368.31% ± 2.49), °Hue (78.57 ± 0.01) and organoleptic values ??(color 4.35; aroma 3.65; taste 4.10; texture 3, 70) with a total value of 9.72% amino acids and the types of amino acids identified are glutamic acids, leucine, aspartic acid, arginine, alanine, phenylalanine, valine, serine, isoleucine, tyrosine, threonine, lysine, histidine, glycine, and methionine. . threonine, lysine, histidine, glycine, and methionine. . threonine, lysine, histidine, glycine, and methionine. Keywords : Flakes, soybean flour, corn flour, pumpkin, characteristics, protein, amino acids.